Intelligent Packaging as a pH-Indicator Based on Cassava Starch with Addition of Purple Sweet Potato Extract (Ipomoea batatas L.) - Rahmadhia, Safinta Nurindra; Saputra, Yanas Anggana; Juwitaningtyas, Titisari; Rahayu, Wahidah Mahanani (Journal Akademik Universitas Swiss German, 2022)
Intelligent packaging is an indicator that has the capability to the condition of packaged foods and their environment through an indicator. This study aims to determine anthocyanin levels, pH sensitivity, solubility, swelling, and water content in intelligent packaging based on cassava starch with the addition of purple sweet potato extract. The method of this research is separated into two stages, which are the extraction of purple sweet potato and the development of indicator film. Furthermore, this research is conducted to analyze the physico-chemical properties of the film. This research is used Completely Randomized Design (CRD) with various extracts on indicator films that are 0%; 5%; 10%; 15% (v/v). The results showed that the indicator film with 15% extract has the best pH sensitivity with the color result 76.07 (L), 23.56 (a), 7.88 (b), solubility 52.15%, swelling power 133.90%, and it has 15.46% water content. The addition of purple sweet potato extracts significantly affected the total anthocyanin of the film indicator and pH sensitivity. The more extracts added to the film, the more obvious the color changes, the higher the water content and solubility but the lower the swelling properties.